Integrating concepts and technologies to advance the study of bird migration. Issue 7 (21st August 2009) - Robinson, W Douglas; Bowlin, Melissa S; Bisson, Isabelle; Shamoun-Baranes, Judy; Thorup, Kasper; Diehl, Robert H; Kunz, Thomas H; Mabey, Sarah; Winkler, David W
Abstract : Recent technological innovation has opened new avenues in migration research – for instance, by allowing individual migratory animals to be followed over great distances and long periods of time, as well as by recording physiological information. Here, we focus on how technology – specifically applied to bird migration – has advanced our knowledge of migratory connectivity, and the behavior, demography, ecology, and physiology of migrants. Anticipating the invention of new and smaller tracking devices, in addition to the ways that technologies may be combined to measure and record the behavior of migratory animals, we also summarize major conceptual questions that can only be addressed once innovative, cutting‐edge instrumentation becomes available.